The destination experience through stopover tourism: Bucharest case study - Gabriela Țigu; Antonio García Sánchez; Cristina Stoenescu; Camelia Gheorghe; Gabriel Cristian Sabou (Amfiteatru Economic Journal, 2018)
Over the years, the evolution of the air transport sector has determined important changes in the tourism industry. One of the consequences of the liberalization of air transport has been the development of the "hub-and-spoke" system, used by traditional airlines in order to be more efficient in a highly competitive environment. As air traffic significantly developed worldwide, "hubs" became highly connected places concentrating an increasing number of transit passengers. At the same time, the liberalization of the airline industry has stimulated both airline and airport competition, therefore, vertical partnerships have become an interesting option for airlines, as well as airports. Moreover, considering that transiting traffic represents a potential tourism market, tourism organizations have also started to get involved in the process. "Stopover tourism" is a new type of tourism based on the partnership between airlines, airports and tourism organizations, with the purpose to turn transiting passengers into stayover tourists. This paper focuses on building a better understanding of how "stopover tourism" type programs can enhance tourism development, identifying the characteristics of this form of tourism and the measures that need to be taken by the authorities in order to encourage its development and investigates the possibility of implementing it in Romania. In order to achieve these objectives, the research was conducted using analysis of secondary data included in several scientific journals and publication, as well as primary data collection, through qualitative research, having as interviewees, experts from the airline industry and from tourism organizations in Romania.
Keywords: L83; L93; M16; M31; O18; R40; Z32; 330; stopover tourism; tourism destination; tourism experience; air transportation; hub